MECHANISMS OF FORMATION AND IMPLEMENTATION OF REGIONAL DEVELOPMENT PROJECTS IN THE UNITED STATES: LESSONS FOR UKRAINE - Torgalo T.O. (Pressing Problems of Public Administration, 2015)
Тhe article summarizes the United States experience in developing and implementingregional development projects. The features of the design of regional development. Determinedbasic mechanisms of formation and implementation of public necessity and project management.